Digital Solution and Programming of Two-Dimensional Thermoelastic Dependent Problems for Transversal Isotropic Bodies - Abduraimov Dostonbek Egamnazar ogli; Turdiev Alisher Pardaboy ogli; Janboev Shohrukh Mamataib ogli; Anorboev Tolibjon Gulom ogli; Jaloliddin Alisher ogli (Research Parks Publishing LLC, 2022)
The need to solve the practical problems of certain phenomena and processes occurring in nature is one of the most important and topical issues today. Such processes can be expressed in mathematical form, solved in the form of algebraic, integral or differential equations or systems of equations. Currently, the use of software is widely used in solving major scientific and economic problems. When studying the software development of complex processes and tasks, the construction and analysis of mathematical models of these objects is becoming more common.